High gain and wideband circularly polarized S‐shaped patch antenna with reactive impedance surface and frequency‐selective surface configuration for Wi‐Fi and Wi‐Max applications. Issue 11 (11th August 2021) - Guthi, Srinivas; Damera, Vakula
Abstract: In this paper, broadband circularly polarized S‐shaped patch antenna is designed with a reactive impedance surface (RIS). Besides the RIS structure, the frequency‐selective surface (FSS) superstrate is deployed to enrich the antenna gain. The S‐shaped patch is modeled on an FR4 glass epoxy and its feed position is set to resonate at 5.3 GHz. The 6 × 6 array size of square patches forms the RIS structure which is inserted in the middle of the S‐shaped patch and ground plane to enhance −10 dB impedance bandwidth and 3 dB axial ratio bandwidth. The 6 × 6 array of unit cells forms the FSS superstrate which is deployed approximately half‐wavelength (≈ λ /2) height above the ground plane to act like a Fabry Perot cavity (FPC) resonator antenna for improving the antenna gain. The combination of RIS and FSS with an S‐shaped patch antenna improves the −10 dB impedance bandwidth, 3 dB axial ratio bandwidth, and the gain simultaneously. The proposed antenna resonates over a wide frequency range with a −10 dB impedance bandwidth of 31.8% (4.81–6.63 GHz) and the antenna has a good 3 dB axial ratio bandwidth of 18.9% (4.99–6.03 GHz). The antenna peak gain is around 10 dBi. The proposed antenna prototype is measured in the anechoic chamber and the measured results mimic the simulation results.